Thare are many methods to prove it.
1st method,
You may use mathematical induction,
P(x)= x^n-a^n,
for n=1, P(x)=x-a is divisible by (x-a)
Let the relation holds true for n=k,
hence, For n=k, P(x)=x^k-a^k=Q(x-a) (Q=some integer){say}
we are to examine whether the relation holds true for n=k+1
For n=k+1,
P(x)= x^(k+1)- a^(k+1)
=x*x^k - a*a^k
=x*x^k - x*a^k + x*a^k - a*a^k
= x(x^k - a^k) + a^k(x-a)
=Qx(x-a) + a^k(x-a)
=(x-a)(Qx + a^k)
Which is divisible by (x-a),
hence the relation holds true for n= any integer
2nd way,
you may use Remainder Theorem, which states that " if a polynomial P(x) is divided by (x-a), then the remainder is P(a)"
according to Remainder theorem,if P(x)=x^n - a^n is divided by (x-a), the remainder is =
Remainder= P(a)= a^n - a^n = 0
hence P(x)=x^n - a^n is divisible by (x-a) for n= any integer
3rd way,
You may use synthetic division to show that when P(x)=x^n - a^n is divided by (x-a) the remainder is zero, but synthetic division is a nightmare for me so I will not personally recommend you to employ it.
4th method,
you may use the method of vanish,
P(x)=x^n - a^n,
putting x=a, P(a)=a^n - a^n=0,
hence (x-a) is a factor of P(x)=x^n - a^n.
5th method,
you may also employ binomial theorem
P(x)=x^n - a^n
={(x-a)+a}^n - a^n
=(x-a)^n+ (nc1)(x-a)^(n-1)*a + (nc2)(x-a)^(n-2)*a^2 + ......+a^n-a^n.
=(x-a)^n+ (nc1)(x-a)^(n-1)*a + (nc2)(x-a)^(n-2)*a^2 + ......+(nc(n-1))(x-a)*a^(n-1)
=(x-a)[(x-a)^(n-1)+ (nc1)(x-a)^(n-2)*a + (nc2)(x-a)^(n-3)*a^2 +......+(nc(n-1))*a^(n-1)]
hence (x-a) is a factor of P(x)
Or,P(x) is divisible by (x-a)
2006-10-26 18:14:08
·
answer #1
·
answered by s0u1 reaver 5
·
0⤊
0⤋
it relies upon on how lots developed you're. sixteen is extremely previous with the aid of be "merely commencing" even nevertheless that's a danger. have you ever had a moist dream yet? if no longer,your physique won't be waiting for this. you are able to email me in case you decide directly to debate youe specific undertaking yet right it is a few uncomplicated suggestion. there's a muscle between yolur legs, in case you peniis is like 0.5 confusing you additionally could make it stiffer by way of tensing this muscle. you should stressful this muscle once you stroke. stressful and stroke for 10 to 20 seconds, then relax some sec, then repreat. speed some million to 2 strokes consistent with 2nd. then in case you start to sense a tingling, or such as you should pee, then do no longer provide up, initiate stroking as speedy as you are able to for as long as you are able to, and which would be sufficient to push you over the sting to climax. wish this facilitates. i'm a be sure.
2016-12-08 21:52:12
·
answer #2
·
answered by gagliano 4
·
0⤊
0⤋
You could use mathematical induction.
X^1-a^1=x-a , so the first case is correct
Suppose X^n-a^n is divisible by(x-a) and we say that X^n-a^n=t .
(x-a)(a^n)is divisible by ,(x-a) and that (x-a)(a^n)=b ; =>
x*t-b=x^(n+1)-a^(n+1) is also divisible by (x-a) =>
"x^n - a^n is divisible by (x-a)" means that "x^(n+1) - a^(n+1) is also divisible by (x-a)" .Problem solved .It's also called the domino principle .
P(a) -> p(a+1) -> p(a+2) -> p(a+3)..............
2006-10-26 07:04:43
·
answer #3
·
answered by d13 666 2
·
0⤊
0⤋
Gjmb's method is certainly quick and easy. Another way to prove this is to just factor it:
x^n - a^n = (x-a) (x^(n-1) + a*x(n-2) + a^2*x(n-3) + a^3*x(n-4) + ... + a^(n-1)*x + a^n))
When you expand the above, you'll see how everything cancels out except the x^n and the -a^n.
2006-10-26 08:59:54
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
When 'n' is even then it can be easily done by applying a^2-b^2=(a-b)*(a+b) recursively, but when 'n' is odd the problem can be solved easily by applying "Binomial Theorem".
Use the series (1-x)^n.
2006-10-29 19:44:30
·
answer #5
·
answered by Napster 2
·
0⤊
0⤋
when n=1 x^n-a^n=x-a divisible by x-a true
let it be true fo some n=k
x^k-a^k is divisible by x-a
let x^k-a^k/(x-a)=c wgere c is element of N
therefore x^k-a^k=c(x-a)
to prove it is true for k+1
x^(k+1)-a^(k+1)=x^k*x-a^k*a
=x[a^k+c(x-a)]-a^k*a
a^k(x-a)+cx(x-a)
(x-a)(a^x+cx)
so p(k+1) is divisible by (x-a)
so true for any n
hence proved
2006-10-26 06:36:45
·
answer #6
·
answered by raj 7
·
0⤊
0⤋
On What
2006-10-26 06:32:04
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
that is easy :
a zero of P(x) is x=a thus x-a is a divisor.
2006-10-26 06:32:58
·
answer #8
·
answered by gjmb1960 7
·
1⤊
0⤋